Grevillea robusta Delayed the Progression of Experimentally Induced Hepatic Fibrosis and Cirrhosis in Wistar Rats by Attenuating the Expression of Smooth Muscle Actin, Collagen, and TGF-β - Hameed, Saaid; Ur Rehman, Atta; Massey, Shazma; Syed, Nawazish-i-Husain; Anwar, Fareeha; Ahmed, Dildar; Ahmad, Sarfraz (Frontiers in Pharmacology, 2022)
The chronic damage of the liver causes the fibrosis especially when the different proteins are accumulated in the liver, which is the basic characteristics of chronic liver damage. The excessive accumulation of the matrix protein like collagen causes the liver fibrosis. Liver fibrosis leads towards the cirrhosis, liver failure and portal vein hypertension. Plants having antioxidant, free radical scavenging activities and anti-inflammatory constituents are believed to be hepatoprotective in nature. Grevillea robusta (GR) is native to subtropical environment. Its in-vitro anti-oxidant, cytotoxic and free radical scavenging activity are known while effect on liver fibrosis and cirrhosis remain elusive. The aim of current study is to evaluate hepatoprotective and anti-fibrotic effects of this plant. GR leaf extract (GREE) was prepared in hydroethanol (70%). Polyphenols and flavonoids contents and in-vitro antioxidant activity of extract was determined. In-vivo hepatitis was induced in wistar rats by continual IP injections of CCl4. GREE was administered by oral gavage at a dose of 100, 300 & 500 mg/kg of body weight once daily for four weeks. Variations in rat’s body weight, liver to body weight ratio, serum alanine aminotransferases, gamma-glutamyl transferase, liver histology and cellular markers of liver fibrosis were evaluated. Serum levels of alanine aminotransferase (ALT) (P<0.05) and gamma glutamyl transferase (γ-GT) (P<0.001) was decreased in treatment group compared to disease control group. RBCs count was increased (P<0.001) in treatment group compared to disease control group. Expression of alpha-SMA was down-regulated to 40% (P<0.05) and collagen was decreased by 9% (P<0.05) compared to disease control. Extracellular matrix deposition and necrotic areas were also decreased as compared to disease control group. It can be concluded that GR possess hepatoprotective action by virtue of antioxidant constituents and delays the progression to liver cirrhosis by suppressing the activation of extracellular matrix producing cells in the liver.